The Role of Trade Unions in Protecting Workers' Rights in The Electricity Sector (Study at PT. PLN Workers Union Persero) - Ali, Muhammad Abrar; Sidi, Redyanto; Mandasari Saragih, Yasmirah (Journal of General Education Science, 2023)
This research discusses the important role of Trade Unions in protecting workers' rights in the electricity sector, with a study focus on the PT Workers Union. PLN (Persero). PT. PLN (Persero) as a company providing electricity services in Indonesia, has a strategic role in the national economy, and the workers' union within it functions as a forum for advocacy, protection and worker representation in various aspects of industrial and employment relations. The research method used in this study is qualitative, with a case study approach to get an in-depth picture of the dynamics and role of the PT Workers Union. PLN (Persero) in protecting workers' rights. Data was collected through document study, in-depth interviews and participant observation, then analyzed using content analysis techniques to identify patterns, themes and key issues related to the role of trade unions in protecting workers' rights. The research results show that the PT. PLN (Persero) has an active and strategic role in protecting workers' rights in the electricity sector. Through advocacy, collective negotiations and educational programs, this trade union contributes to creating fair, safe and conducive working conditions for workers, as well as fighting for workers' rights, such as adequate remuneration, welfare guarantees and legal protection for workers. However, there are also several obstacles and challenges faced by trade unions in carrying out their roles, which require further strategies and efforts to overcome.